Polyamidoxime-based graphene oxide ultrathin film material and method for efficiently extracting uranium
By using polygamidoxime-based graphene oxide ultra-thin film material in seawater, the problems of poor salt shrinkage and poor mass transfer are solved, and the high-efficiency uranium adsorption and rapid uranium extraction are achieved, which is suitable for the industrialization of uranium in seawater. application.
Patent Information
- Application Number
- CN202411279116.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
When extracting uranium in seawater, the existing amidoxime-based adsorbents are low in uranium due to poor salt shrinkage resistance and poor mass transfer properties, which leads to low uranium adsorption efficiency and difficult to be used in industrial use.
Using the preparation method of polygemine oxime-based graphene oxide ultrathin film material for efficient uranium extraction, the film is formed by dropping the mixture solution on the water surface, and the phase separation process is driven by the Marangori effect to prepare nanosheets with parallel arrangement and grading. Ultra-thin film material with pore structure and excellent salt shrinkage resistance.
It has achieved efficient uranium adsorption under light conditions, with an uranium adsorption capacity of 803.73 mg g-1 quickly, and has good mechanical properties and salt shrinkage resistance. It is suitable for seawater uranium extraction applications.
Smart Images

Figure CN119114030A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of novel functional materials, and in particular to a polyamidoximine-based graphene oxide ultra-thin film material and method for efficient uranium extraction. Background Art
[0002] The importance of uranium to the nuclear industry and the limited supply of uranium ores on land make it imperative to develop unconventional uranium resources, such as seawater uranium extraction. Given that the uranium reserves in the world's oceans (4.5 billion tons) are almost 1,000 times that of terrestrial resources, seawater uranium extraction makes it possible to ensure the sustainable development of the nuclear industry. However, the practical implementation of this strategy is hindered by the low uranium concentration in seawater (~3.3 ppb) and the large number of competing ions in the ocean. Therefore, seawater uranium extraction is regarded as one of the seven major chemical separation technologies that will change the world. Over the past 60 years, considerable efforts have been made to explore adsorbents for extracting uranium from seawater. In particular, amidoxime-based adsorbents have attracted attention due to their good binding affinity and selectivity for uranyl ions, but have not yet been industrialized due to their low uranium extraction efficiency. The uranium extraction efficiency of these adsorbents is limited by their poor resistance to salt shrinkage and poor mass transfer, which leads to channel blockage that hinders uranyl ions from entering the internal structure, ultimately resulting in inefficient utilization of the functional groups of the adsorbent.
[0003] The adsorption efficiency of uranium can be potentially improved by internal microstructure design and the use of external applied stimuli, such as light fields and electric fields. Among these stimuli, light has the greatest application potential due to the abundant sunlight on the ocean surface and the endothermic nature of the uranium adsorption process. The addition of photothermal conversion components to the adsorbent can convert the energy of sunlight into thermal energy, promote the coordination of the adsorbent functional groups to uranyl ions, and thus improve the adsorption capacity and adsorption rate. Therefore, the challenge of extracting uranium from seawater can be solved by designing adsorbents with high photothermal conversion efficiency.
[0004] Graphene oxide (GO) nanosheets can provide ultra-thin films, unique photothermal properties and simple layer-by-layer self-assembly, thus making certain progress in uranium adsorption performance. For example, a Chinese patent CN202110968626.1 applied for by our research group discloses an ordered lamellar polyamidoximine-based graphene oxide composite material for uranium extraction from seawater and its preparation method. Although the lamellar ordered macroporous structure can be prepared by the ice template method, making the composite material have ultra-high hydrophilicity and water permeability, thereby improving the uranium adsorption efficiency, low-temperature freezing leads to an increase in the manufacturing cost of the adsorbent, which poses a challenge to the large-scale preparation of adsorbents. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction, which solves the problem of low uranium adsorption efficiency caused by poor salt shrinkage resistance and mass transfer of existing amidoxime-based adsorbents.
[0006] On the one hand, the present invention adopts a preparation method of a polyamidoxime-based graphene oxide ultra-thin film material for efficient uranium extraction, comprising the following steps: adding graphene oxide nanosheets to a polyamidoxime solution according to a certain mass ratio and stirring evenly to obtain a mixture solution; then taking the mixture solution and dripping it onto a water surface above the water surface to form a film, taking it out and drying it to obtain a polyamidoxime-based graphene oxide graphene ultra-thin film material; the weight ratio of the graphene oxide nanosheets to the polyamidoxime solution is 2-4%; the density of the polyamidoxime in the polyamidoxime solution in an N'N-dimethylformamide solvent is 0.81-0.93 g / cm 3 .
[0007] Preferably, the weight ratio of graphene oxide nanosheets to polyamidooxime solution is 4%; the density of polyamidooxime in N'N-dimethylformamide solvent in the polyamidooxime solution is 0.93 g / cm 3 .
[0008] Preferably, the amount of polyamidoxime used is 5 g, and the amount of graphene oxide used is 0.1-0.2 g.
[0009] Preferably, the polyamidooxime solution is prepared by the following method: weigh hydroxylamine hydrochloride and dissolve it in N'N-dimethylformamide, then add sodium hydroxide and sodium carbonate and stir evenly, and then add polyacrylonitrile to carry out oximation reaction to obtain the polyamidooxime solution.
[0010] Preferably, the mixture solution is dropped at a position 1-3 cm above the water surface to form a film.
[0011] Preferably, the amount of the mixture solution is 10 μL.
[0012] Preferably, the graphene oxide is 1-10 μm wide.
[0013] The method for preparing the polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction provided by the present invention has the advantages of simple process, mild conditions, economy and high efficiency.
[0014] Furthermore, the polyamidoximine-based graphene oxide material prepared by the Marangoni effect-driven phase separation process has the advantages of parallel-arranged nanosheets, ultra-thin thickness (10 μm) and hierarchical pore structure (21.36 μm macropores and 0.12 μm micropores), good mechanical properties (tensile strength of 2.54 MPa), excellent resistance to salt shrinkage and rapid uranyl ion transport (adsorption equilibrium is reached within 6 days). Under light conditions, the uranium adsorption capacity of the SSPG4 film in a solution containing 8 ppm uranium is as high as 803.73 mg g·m. -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1FT-IR image of polyamidoximate in Example 1;
[0016] Figure 2 A is the SEM image of SSPG4 film. Figure 2 B is the SEM image of BCPG4 film;
[0017] Figure 3 TEM image of SSPG4 film;
[0018] Figure 4 The test results of uranium adsorption performance of the thin film materials prepared in Examples 1 to 6 and Comparative Example 3 under light / darkness;
[0019] Figure 5 Photos of original, alkali-treated and uranium-containing BCPG4 and SSPG4 films (a); Schematic diagram of the salt shrinkage resistance of BCPG4 and SSPG4 films (b); SEM images of BCPG4 and SSPG4 films before and after uranium adsorption (c);
[0020] Figure 6 Schematic diagram of uranium adsorption kinetics of SSPG4 and BCPG4 films under light / darkness, respectively. DETAILED DESCRIPTION
[0021] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0022] Polyacrylonitrile (PAN, Mw = 150000, 99%) was purchased from MacLean Chemical Co., Ltd., and graphene oxide nanosheets and graphene oxide were purchased from Carbene Technology Co., Ltd., with a lateral size of 1-10 μm.
[0023] Embodiment 1: A polyamidoximine-based graphene oxide ultra-thin film material and method for efficient uranium extraction, specifically comprising the following steps:
[0024] S101: 12 g of hydroxylamine hydrochloride was dissolved in 100 mL of N'N-dimethylformamide (DMF); 3.0 g of sodium hydroxide and 3.9 g of sodium carbonate were added to the above solution, and mechanically stirred at 45°C for 3 hours at a speed of 400 r / min; 10 g of polyacrylonitrile was added to the obtained mixture, and mechanically stirred at 65°C for 18 hours at a speed of 400 r / min; the reaction product was cooled to room temperature and centrifuged at a speed of 10000 r / min, and the light yellow supernatant was collected to obtain a polyamidooxime (PAO) solution; the density of the polyamidooxime content in the polyamidooxime (PAO) solution in the N'N-dimethylformamide solvent was calculated to be 0.93 g / cm 3 .
[0025] S102: 0.2 g of graphene oxide nanosheets were added to 5.0 g of polyamidoximate solution, stirred for 1 h and ultrasonicated for 20 min to obtain GO / PAO solution;
[0026] S103 takes 10 μL of the obtained mixture and drops it onto the water surface at a distance of 3 cm from the water surface. After keeping it on the water surface for 20 minutes, it is taken out. The formed film is taken out and dried at 45°C to obtain a polyamidoximine-based graphene oxide graphene ultra-thin film material, named SSPG4.
[0027] Examples 2 to 6: The difference between Examples 2 to 6 and Example 1 is that the amount of graphene oxide used is different. The amount of graphene oxide in Examples 2 to 6 is 0, 0.05g (1wt%), 0.1g (2wt%), 0.15g (3wt%), and 0.25g (5wt%), respectively. The finally prepared materials are named SSPG0, SSPG1, SSPG2, SSPG3, and SSPG5, respectively.
[0028] Comparative Example 1: Effect of polyamidooxime (PAO) solutions prepared with different parameters on the film formation of polyamidooxime-based graphene oxide ultra-thin film materials. As shown in Table 2, it is found that the film formation of polyamidooxime (PAO) solutions prepared with different amounts of DMF in Example 1 is different. The density of polyamidooxime in N'N-dimethylformamide solvent is calculated to be 0.81-0.93 g / cm 3 The film formation is good within the range.
[0029] Table 1 Effect of polyamidoximine (PAO) solutions prepared with different parameters on the film formation of polyamidoximine-based graphene oxide ultra-thin film materials.
[0030] DMF addition amount Density of PAO Film formation 50mL 1.35 No dripping film 100mL 0.93 Good film formation 150mL 0.81 Good film formation 200mL 0.72 No dripping film 250mL 0.6 No dripping film
[0031] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the drop height is 4 cm, and it is found that no film can be formed. Therefore, the drop height is preferably 1-3 cm.
[0032] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the PAO / GO film is prepared by blade coating technology.
[0033] The GO / PAO solution was placed on a glass plate and moved with a scraper at a constant speed to form a liquid film. The glass plate was then immersed in pure water for 20 min and dried at 45 °C for phase separation to obtain a BCPG4 film.
[0034] The polyamidoximine-based graphene oxide film material prepared in Example 1 was characterized and its performance tested, and the results were as follows:
[0035] (1) Polyamidoximes were characterized by Fourier transform infrared spectroscopy (FT-IR). Figure 1As shown, the product shows the following characteristic absorption peaks: C=N (1645cm -1 )、N–O(943cm -1 ), C≡N(2246cm -1 ) disappeared, indicating the successful synthesis of polyamidoximate.
[0036] (2) The SSPG4 film of Example 1 and the BCPG4 film of Comparative Example 3 were characterized using a field emission scanning electron microscope (SEM). The results are as follows: Figure 2 As shown, the SSPG4 film has a two-layer hierarchical porous structure with macropores (in the water contact layer) and micropores (in the air contact layer) substructures, while the BCPG4 film with the same GO content exhibits a relatively irregular mesoporous structure. Further pore size distribution analysis shows that the average diameters of the macropores and small pores of SSPG4 are 21.36 μm and 0.12 μm, respectively, while the BCPG4 film has pores with an average diameter of 2.83 μm. The macroporous structure of SSPG4 is more conducive to the entry of uranium ions into the interior of the film than the mesoporous structure of the BCPG4 film. The specific surface areas of SSPG4 and BCPG4 films are 13.64 and 2.53 m 2 g -1 , indicating that the SSPG4 film has a larger area, which can promote the contact between the site and the uranium ions.
[0037] Compared with the BCPG4 film thickness of 100.01 μm, the SSPG4 film thickness is smaller (9.418 μm). Although the SSPG4 film has a low thickness and high porosity, it still exhibits high mechanical strength (high tensile strength of 2.54 MPa) in a wet state, indicating that the polyamidoximine-based graphene oxide film material prepared by the method of the present invention has ultra-thin characteristics and good mechanical properties, which is more conducive to uranium extraction applications.
[0038] (3) SSPG4 was characterized using transmission electron microscopy (TEM). Figure 3 As shown, the TEM image of SSPG4 shows parallel graphene oxide nanosheets, which is beneficial for the transport of uranyl ions and the photothermal conversion performance.
[0039] (4) The thin film materials prepared in Comparative Example 3 and Examples 1 to 6 were characterized and tested for uranium extraction performance. The results are shown in Table 2. The SSPG4 ultra-thin film material exhibited a good hierarchical structure and a high GO content. In the range of 0-4wt%, a uniform film (10μm) could be obtained, but the film prepared at 5wt% was relatively thick (50μm) and could not be spread, and was uneven.
[0040] As the amount of graphene oxide increased from 1 wt% to 4 wt%, the adsorption performance increased gradually under light conditions and decreased gradually under dark conditions. The highest uranium adsorption capacity was 803.73 mg g in 8 ppm uranium-containing simulated seawater solution at pH 6 under light conditions. -1 .
[0041] Table 2 Characterization of thin film materials prepared in Examples 3 and 1 to 6 and test results of uranium extraction performance
[0042]
[0043] (5) SSPG4 film shows excellent resistance to salt shrinkage
[0044] like Figure 5 As shown in Figure a, the areas of the original SSPG4 and BCPG4 films decreased by 13.8% and 77.3% respectively after alkali treatment (immersion in 20 mM NaOH for 10 min) and uranium adsorption (immersion in 8 ppm uranium-containing simulated seawater solution for 6 d). This is because the small pore structure of the SSPG4 film provides support and prevents the shrinkage of the macropore structure, as shown in Figure 5. Figure 5 As shown in b. Figure 5 The SEM image of c further verifies that the channels of the BCPG4 film are basically blocked during the uranium adsorption process due to salt shrinkage, which hinders the migration of uranyl ions from the solution to the adsorbent. Based on the excellent resistance of SSPG4 film to salt shrinkage, it still maintains its porous structure after uranium adsorption, which greatly promotes the contact between uranyl ions and functional groups.
[0045] (6) SSPG4 film shows high efficiency in uranium extraction
[0046] like Figure 6 The results showed that the time required for SSPG4 and BCPG4 films to reach dynamic saturation equilibrium was 6 and 20 h, respectively. The uranium adsorption capacity of SSPG4 film under dark and light conditions was 467.29 and 803.73 mg g -1 ), indicating that the SSPG4 film has a high uranium adsorption capacity and a faster uranium extraction rate.
[0047] In summary, the method of preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction provided by the present invention is simple in process, mild in conditions, economical and efficient, and a layered ultra-thin SSPG film with aligned parallel GO nanosheets is prepared by super diffusion technology driven by the Marangoni effect, and has the performance of efficient uranium extraction. Different from the BCPG film prepared by the traditional blade coating method, the SSPG film has the advantages of neatly arranged GO nanosheets, ultra-low thickness and hierarchical pore structure, good mechanical properties, efficient photothermal conversion and rapid uranyl ion transport, and the uranium adsorption capacity under light conditions is as high as 803.73 mg g -1 The uranium adsorption capacity of SSPG4 film in seawater containing 8 ppm uranium is 1.56 times that of BCPG4 film under the same conditions. In addition, SSPG4 film shows excellent resistance to salt shrinkage, which is beneficial to its application in actual seawater uranium extraction.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction, characterized in that The method comprises the following steps: adding graphene oxide nanosheets to a polyamidoxime solution in a certain mass ratio and stirring the mixture solution to obtain a mixture solution; then taking the mixture solution and dropping it onto a water surface to form a thin film, taking it out and drying it to obtain a polyamidoxime-based graphene oxide graphene ultra-thin film material; the weight ratio of the graphene oxide nanosheets to the polyamidoxime solution is 2-4%; the density of the polyamidoxime in the polyamidoxime solution in an N'N-dimethylformamide solvent is 0.81-0.93 g / cm 3 .
2. The method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction according to claim 1, characterized in that: The weight ratio of the graphene oxide nanosheets to the polyamidooxime solution is 4%; the density of the polyamidooxime in the polyamidooxime solution in the N'N-dimethylformamide solvent is 0.93 g / cm 3 .
3. The method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction according to claim 1, characterized in that: The amount of the polyamidoxime used is 5 g, and the amount of the graphene oxide used is 0.1-0.2 g.
4. The method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction according to claim 1, characterized in that: The polyamidooxime solution is prepared by the following method: weighing hydroxylamine hydrochloride and dissolving it in N'N-dimethylformamide, then adding sodium hydroxide and sodium carbonate and stirring evenly, and then adding polyacrylonitrile to carry out oximation reaction to obtain the polyamidooxime solution.
5. The method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction according to claim 1, characterized in that: The mixture solution is dropped at a position 1-3 cm above the water surface to form a film.
6. The method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction according to claim 3, characterized in that: The amount of the mixture solution used is 10 μL.
7. The method for preparing a polyamidoximine-based graphene oxide ultra-thin film material for efficient uranium extraction according to claim 1, characterized in that: The graphene oxide is 1-10 μm wide.
8. A polyamidooxime-based graphene oxide ultra-thin film material for efficient uranium extraction prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
Ultra-thin solid electrolyte film and preparation method thereof
CN105406097A
Porous hydrogel film for extracting uranium from seawater and preparation method of porous hydrogen film
CN110684233A
Amidoxime-based modified graphene oxide material and preparation method thereof
CN111518248A
Ordered lamellar polyamidoxime-based graphene oxide composite material for extracting uranium from seawater and preparation method thereof
CN113694902A
Uranium-adsorbing polydopamine modified PAO film material and preparation method thereof
CN114849661A
